2016
DOI: 10.1515/jpem-2015-0255
|View full text |Cite
|
Sign up to set email alerts
|

First case report of rare congenital adrenal insufficiency caused by mutations in the CYP11A1 gene in the Czech Republic

Abstract: We characterized a case of congenital adrenal insufficiency caused by cholesterol side-chain cleavage enzyme (P450scc) deficiency. The patient presented after birth with cardiopulmonary instability, hyponatremia, hyperkalemia, hypoglycemia and metabolic acidosis. We confirmed primary adrenal insufficiency. There were no signs of the external genitalia virilism. The replacement therapy with glucocorticoids and mineralocorticoids led to normal laboratory results. At the age of 12 years, we confirmed hypergonadot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…AI has two different expression forms: classical and nonclassical (Pomahacova et al. ). The classical phenotypic spectrum ranges from miscarriage and prematurity during pregnancy, to complete under‐androgenization and severe early or late onset adrenal failure at postnatal stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AI has two different expression forms: classical and nonclassical (Pomahacova et al. ). The classical phenotypic spectrum ranges from miscarriage and prematurity during pregnancy, to complete under‐androgenization and severe early or late onset adrenal failure at postnatal stages.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital AI is an autosomal recessive disorder characterized by elevated ACTH and plasma renin levels with low or absent adrenal steroids. AI has two different expression forms: classical and nonclassical (Pomahacova et al 2016). The classical phenotypic spectrum ranges from miscarriage and prematurity during pregnancy, to complete under-androgenization and severe early or late onset adrenal failure at postnatal stages.…”
Section: Discussionmentioning
confidence: 99%
“…Although in majority of the cases, there was a correlation of external genital development and onset of adrenal failure with enzyme activity level, it was not perfect 4–16. Few patients with 46,XY and relatively lower enzyme activity level had normal external genitalia whereas few patients with normal enzyme activity or heterozygous mutation had abnormal genitalia.…”
Section: Discussionmentioning
confidence: 89%
“…However, there was better correlation between age at onset of adrenal failure and genital phenotype among 46,XY CYP11A1 deficiency children 1 4–16. 46,XY children with normal or slightly ambiguous male external genitalia had later onset of adrenal insufficiency when compared to those with female or severely ambiguous external genitalia who had their presentation in neonatal or early infancy period 1 4–16. Recent studies have identified a large number of CYP11A1 deficiency patients among those with apparent primary adrenal insufficiency without disorder of sex development 1 17–20.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, loss of StAR function affects the first step of steroidogenesis, inhibiting all steroid production in adrenal glands and gonads, leading to the most serious form of CAH, lipoid congenital adrenal hyperplasia (LCAH, OMIM 201710) ( Kaur et al, 2016 ; Ullah et al, 2020 ). Most LCAH result from loss-of-function mutations in the double allele STAR gene, while a few are caused by CYP11A1 gene mutations ( Sahakitrungruang et al, 2011 ; Pomahačová et al, 2016 ). LCAH can be divided into classic and non-classic forms ( Garg et al, 2020 ), with the classic form characterized by severe glucocorticoid and mineral corticosteroid deficiency at birth, as well as female or minimally male external genitalia regardless of the sex chromosome.…”
Section: Introductionmentioning
confidence: 99%